Influence of Schroth Best Practice Therapy on Ventilatory Function in Adolescent Idiopathic Scoliosis: Randomized Controlled Study Design - Hegazy, Alaa Abdelmonem Ahmed; Sayed, Akram Abd El Aziz; Rahmy, Awny Fouad; Elsayed, Mahmoud Ibrahim; Shauosh, Ali Mohamed Mohamed; Negm, Mohamed AbdelMonem (International Journal of Membrane Science and Technology, 2023)
Introduction: Approximately 2%-3% of the population develops idiopathic scoliosis, making it the most prevalent structural spinal deformity in children as well as adolescents. Objective: To find out the efficacy of Schroth Best Practice therapy on pulmonary functions in adolescent idiopathic scoliosis. Methods: Sixty female subjects with adolescent idiopathic scoliosis were recruited from Outpatient Department at AlKasr Al-Ainy Hospital from May 2022 to July 2023 were enrolled in that study. They were randomized into two equivalent groups: Either the intervention group: Group A (Study group) consists of 30 subjects received the Schroth Best Practice exercises program for 18 weeks, or the control group Group B: consists of 30 subjects received traditional exercise program for 18 weeks. Both groups were given 3 sessions a week. Both groups received assessment of pulmonary functions: Forced Vital Capacity (FVC), forced expiratory volume in the first second (FEV1) As well as Peak Expiratory Flow (PEF) on 1st and 18th week. Measuring pulmonary function with digital handheld spirometer before and after treatment. These selective subjects were randomized into two equal groups. Results: There was a statistically significant difference (p<0.05) among the two groups when comparing the mean values of all measured variables pre and post treatment. All analyses were performed at the 0.05 level of significance. With the initial alpha level set at 0.05, in favor of group A. Conclusion: Both Schroth Best Practice exercise program and traditinal exercise program have a significant effect in adolescent idiopathic scoliosis, and the integrated Schroth Best Practice exercise program was more effective than traditional exercise alone.